Amelia Of Hind Limbs In A Buffalo Calf - A Case Report - Jethva, P.C.; Patel, S.B.; Manohar , B.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Amelia - the total absence of limbs - is a rare congenital malformation diagnosed in domestic animal neonates. In cattle, only cases of hemimelia (the absence of a portion of a limb) and deformities of hind limbs have been reported recently by Lapointe et al. (2000) and Vermunt et al. (2000). Congenital defects are structural or functional abnormalities and can affect on isolated portion of a body system, entire system or parts of several systems and may cause obstetrical problems (Long, 2001). Limb deficiency defects are relatively rare, particularly in chromosomal aberrations such as segmental autosomal monosomies or trisomies. The etiology of limb malformation includes genetic factors, environmental agents or a combination of both (Newman et al., 1999). In humans, some limb anomalies are inherited, and genes responsible for the anomalies have been identified. There are also reports indicating that chromosomal aberrations are associated with congenital limb malformations (Manouvrier-Hanu et al., 1999). This communication places on record such a rare case of hind limb Amelia in a buffalo calf.